Prostatic cyst in a pediatric patient with autosomal dominant polycystic kidney disease. Issue 2 (1st February 2021) - Colaco, Marc; Cannon, Glenn M; Moritz, Michael L
Abstract : Autosomal dominant polycystic kidney disease (ADPKD) is the most common inheritable form of renal cystic disease and is associated with cysts in other organs. Prostatic cysts are rare though and have not been reported in the paediatric population. Reported is the presence of a prostatic cyst that was incidentally noted on routine sonogram in a 15 year old with ADPKD.